Tinta roja : el periodismo liberal en Bogotá, 1890-1900 (2014)
ABSTRACT: Some of the journals in the Regeneration were defined as strong opponents of the regime and for this reason they were censured, suspended and fined. This article analyzes the existing ideology in the opposition press from 1890 to 1900 and it studies the content and form of four of the most recognized newspapers for their criticism of the government or the mainstream parties. It also notes the proposals indirectly suggested in their pages.